A Productive-Creative Work Ethic Model Based on Hadith: A Thematic Analysis - Idris Baidhowi; Siti Laelatul Alviah; Suleyman Tagiyev; Maylani Salsabila; Hadid Fatah Alviah (Yayasan Albahriah Jamiah Indonesia, 2026)
Strengthening the productive-creative work ethic in contemporary Muslim society is hindered by a gap between the normative teachings of the hadith and the practical needs of the modern workplace, which demand professionalism and innovation. Several studies show that the study of hadith on work remains partial and has not yet developed a systematic, operational conceptual framework. This study aims to formulate a conceptual-operational model of a productive-creative work ethic, grounded in the Prophet’s hadith, through an integrated thematic approach. The method used is qualitative literature research with a mawḍūʻī approach, including the stages of takhrīj of hadiths, thematic classification of hadiths on work, productivity, professionalism, and creativity, and a contextual-synthetic analysis to build a coherent conceptual framework. The results of the study indicate the formation of a three-dimensional integrative work ethic model: first, work as productive worship oriented towards the values ​​of usefulness, sincerity, and social responsibility; second, professionalism based on the principles of itqān, trust, and competence that emphasizes quality, accuracy, and accountability of work; Third, creativity and innovation as an effort to adaptively renew methods, strategies, and optimize potential within normative values. These three dimensions are structured within a systemic, interrelated, and applicable framework. It is concluded that the Prophet’s hadith provides both a normative and operational basis for developing a productive-creative work ethic that is relevant to modern demands and contributes to strengthening the methodology of constructive thematic hadith studies.